Sexualidade e neopentecostalismo: representação de jovens da Igreja Evangélica Bola de Neve - Dantas, Bruna Suruagy do Amaral (2006)
The research here developed analyzed the representations of sexuality present in the speeches of young Christians,members of the Evangelical Church Bola de Neve. The ecclesiastical institution's preoccupation with the laity's sexual life is evident. Sexuality is disguised subtle in pastoral sermons and advice. Sexual behavior finds itself under the church's tutelage, which tries to moralize and set regulations upon it. In order to understand the symbolic findings of the young parishioners in relation to the sexuality phenomenom, we attended cults every week for one year, participated in a few meetings, attended baptismal ceremonies, visited the church's site, and carried out interviews with seven individuals who belong to the religious community for more than one year. After collecting the data, we organized the speeches in thematic nuclei, defined upon work objectives and theoretical references. In order to analyze the obtained material, we used the Social Representation Theory, elaborated by Serge Moscovici. The data pointed out the young people' s conceptions of sexuality and to the official discourse of the church. Singles' sexual life turns into an obsession to the clerical hierarchy that tries to set regulations on romantic relationships. While the desire is obstructed, the laity's bodies parade freely through the temple, exhibiting their beautiful curves. The libido is, thus, simutaneously, inhibited and stimulated in the religious space. The institutional contradiction is flagrant